Komunikasi Teks ke Visual: Kerangka Teoretis Gamifikasi Untuk Pembelajaran - Komarudin; Fatkha, Magfirotul; Sujono, Ujon (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2025)
This study examines aspects of visual design and game element concepts within the framework of enhancing the learning experience and student motivation. The focus is on traditional Al-Qur'an education, where learning is often textual and monologic, thus tending to decrease student learning motivation. This article develops a theoretical framework for the gamification of Al-Qur'an learning that integrates interactive visual elements to improve student engagement. The research method is a literature review based on Design-Based Research (DBR), a research paradigm that systematically designs, develops, and evaluates practical solutions. The results of the study produce a gamification design that considers Islamic values and the characteristic needs of the digital generation. The proposed framework includes a needs-based adaptive process, the utilization of digital platforms, and the strengthening of Islamic narrative elements. With appropriate design, gamification can transform Al-Qur'an learning from static text into an enjoyable visual experience, thereby expected to increase learning motivation in Islamic educational environments.